Comparative analysis of mesenchymal stromal cells derived from rabbit bone marrow and Wharton's jelly for adipose tissue engineering. (1st November 2020) - Li, Linli; Dong, Jian; He, Yiqun; Mao, Wei; Tang, Han; Dong, Youhai; Lyu, Feizhou
ABSTRACT: Purpose : To investigate the proliferative, adipogenic, and immunological properties of rabbit Mesenchymal stromal cells (MSCs) derived from bone marrow and umbilical cord Wharton's jelly.Materials and Methods : We extracted rabbit MSCs from bone marrow (BMSCs) and umbilical cord Wharton's jelly (WJ-MSCs). Both BMSCs and WJ-MSCs underwent adipogenic differentiation for 2 weeks, and then were transferred to non-inductive complete medium. Their adipogenic capacities were examined by histomorphometry and quantitative RT-PCR (qRT-PCR). The immunological markers were determined by mRNA expression of MHC-Ia, MHC-II, and RLA-DRA by qRT-PCR and protein expression of MHC-II by immunofluorescent staining. The proliferative capacities of adipogenic MSCs were also examined by counting kit-8 experiment and cell population doubling time.Results : We found that adipogenic differentiation increased the mRNA expression levels of adipogenic and immunological markers. The protein expression levels of MHC-II also increased after adipogenic differentiation in both groups. The adipogenic BMSCs showed higher mRNA expression levels of adipogenic and immunological markers. Removal of adipogenic agents after 2 weeks of adipo-differentiation inversely decreased the expression of immunological and adipogenic markers. The adipo-differentiation could decreased the proliferative capacities of both MSCs, but the adipogenic WJ-MSCs showed significantly higher proliferative capacities than BMSCs.Conclusions : Adipogenic differentiation increased the immunogenicity of both BMSCs and WJ-MSCs, and dedifferentiation inversely decreased their immunogenicity. Adipogenic WJ-MSCs showed significantly higher proliferative and immunoprivileged capacities than BMSCs, and the dedifferentiated BMSCs showed almost the same adipogenic capacity as WJ-MSCs. WJ-MSCs were more suitable than BMSCs for adipose tissue engineering.